Instilling Religious Character through Recitation of Al-Qur'an Juz 30 at Madrasah Ibtidaiyah Bustanul 'Ulum Lampung Tengah - Abit Masruri; Miftahur Rohman (Episteme: Jurnal Kajian Mahasiswa, 2025)
Children are a trust from Allah SWT and the future generation with great potential. Early education is vital for their growth, benefiting both families and society. In the era of globalization, technological advances present challenges, including diminishing religious discipline. Islamic education, especially through Tadarus Al-Qur'an, plays a key role in instilling religious values. This research examines the implementation of Tadarus Al-Qur'an Juz 30 at MI Bustanul 'Ulum Jayasakti to instill religious character values and identify challenges teachers face. A qualitative approach, using interviews, observation, and documentation, was employed. The findings show various methods, including daily habituation and teacher examples, to instill values like responsibility and perseverance. Challenges include limited time, varying motivation, and external influences, though support from school policies and parents helps strengthen these values.